Innovative transformation of school nutrition in the context of inclusion: opportunities of electronic systems - Kuzmin, Dmytro; Soldatova Oksana; Kuzmin, Anton; Niemirich, Oleksandra; Kuzmin, Oleg (My University, 2025)
The article addresses the issue of digital transformation of school nutrition systems in Ukraine within the framework of an inclusive approach. The study focuses on the functional capabilities of the electronic food management system “SUPiK 2,” which provides comprehensive automation of menu planning, inventory control, technological card development, and compliance with individual dietary requirements. У статті розглянуто питання цифрової трансформації системи шкільного харчування в Україні в контексті впровадження інклюзивного підходу. Основну увагу зосереджено на функціональних можливостях електронної системи управління харчуванням «СУПіК 2», яка забезпечує автоматизацію процесів планування меню, обліку продуктів, формування технологічних карт і контролю відповідності індивідуальним дієтичним потребам споживачів.
Keywords: кафедра технології ресторанної і аюрведичної продукції; інклюзивне харчування; шкільне харчування; персоналізоване меню; inclusive nutrition; school nutrition; electronic management; personalized menu